Breaking Barriers: The Role of 'Professional English and Communication' Courses in Medical Education - Lamara Kadagidze (European Scientific Journal, ESJ, 2024)
The present paper explores the significant role of effective English communication in enhancing the physician-patient relationship in multicultural healthcare settings. The primary objective is to evaluate the impact of a specialized "Professional English and Communication" course on the communication skills of medical students at East-West Teaching University in Tbilisi, Georgia. Employing a mixed-methods approach, the study included a quantitative survey and qualitative feedback from a cohort of 11 students, both native and non-native speakers, enrolled in the Medical Doctor One-Cycle Educational Program. During the 13-week course, students engaged in role-plays and discussions based on structured scenarios. Findings indicated the high effectiveness of the course, with students rating it as significantly impactful in improving their professional English and communication skills. Notably, students reported increased engagement and comfort in participating in class activities following the implementation of structured guidelines for role-plays. The study concludes by affirming the value of targeted communication skills training in medical education, particularly through practical activities such as role-plays. Feedback also highlighted the importance of a supportive and inclusive learning environment in promoting engagement and overcoming challenges. These findings have implications for designing similar courses to cater to diverse student populations in the medical field. Further research should explore the long-term impact of such courses on students' professional practices and patient outcomes.